Customer Relationship Marketing and Customer Satisfaction: A Study on Mobile Service Providing Companies in Sri Lanka (Global Journal of Management and Business Research, 2012)
In the present era, customer relationship marketing plays a vital role. The major goals of customer relationship marketing can be expressed simply as understanding and treating customers better for increased loyalty and profit. Main purpose of the study is examining the relationship between customer relationship marketing and customer satisfaction. Customer relationship marketing can be measured through following ten variables trust, commitment, empathy and equity. Data were collected through a seven points Likert type summated rating scales of questionnaire. A sample of one hundred and seven customers was surveyed from three mobile service providing companies such as Airtel, Dialog, and Mobitel. Correlation and regression analyzed has been employed to measure relationship and contribution among the dependent and independent variables.
Keywords: Customer relationship marketing; customer satisfaction; service quality